(3EJaGb GdJMcje hGdeTcdGJ GdYedjI hGdbGfhfjI aj GdYdGbGJ GdNGUI GdOhdjI (B/s - (3GdQaGYj, CTQa YHO GdYdjes ((3GdEScfOQjI(B: s (3OGQ GdacQ GdYQHj(B, s, 2002)
(3eaghe GdfXGe GdYGe GdOGNdj(B- (3eaghe GdJMcje(B- (3eTGcd GdfXGe GdYGe aj GdYdGbGJ GdYGeI(B- (3eTGcd GdfXGe GdYGe aj YdGbJg HGJaGb GdJMcjes
Keywords: (3GdJMcjes; (3GdYdGbGJ GdYGeIs